Absorption and chemopreventive targets of sulforaphane in humans following consumption of broccoli sprouts or a myrosinase‐treated broccoli sprout extract. Issue 3 (22nd January 2015) - Atwell, Lauren L.; Hsu, Anna; Wong, Carmen P.; Stevens, Jan F.; Bella, Deborah; Yu, Tian‐Wei; Pereira, Clifford B.; Löhr, Christiane V.; Christensen, John Mark; Dashwood, Roderick H.; Williams, David E.; Shannon, Jackilen; et al.
<x xml:space="preserve">Abstract</x> Scope Sulforaphane (SFN), an isothiocyanate derived from crucifers, has numerous health benefits. SFN bioavailability from dietary sources is a critical determinant of its efficacy in humans. A key factor in SFN absorption is the release of SFN from its glucosinolate precursor, glucoraphanin, by myrosinase. Dietary supplements are used in clinical trials to deliver consistent SFN doses, but myrosinase is often inactivated in available supplements. We evaluated SFN absorption from a myrosinase‐treated broccoli sprout extract (BSE) and are the first to report effects of twice daily, oral dosing on SFN exposure in healthy adults. Methods and results Subjects consumed fresh broccoli sprouts or the BSE, each providing 200 μmol SFN daily, as a single dose and as two 100‐μmol doses taken 12 h apart. Using HPLC‐MS/MS, we detected ∼3 x higher SFN metabolite levels in plasma and urine of sprout consumers, indicating enhanced SFN absorption from sprouts. Twelve‐hour dosing retained higher plasma SFN metabolite levels at later time points than 24‐hour dosing. No dose responses were observed for molecular targets of SFN (i.e. heme oxygenase‐1, histone deacetylase activity, p21). Conclusion We conclude that the dietary form and dosing schedule of SFN may impact SFN absorption and efficacy in human trials.